IMPLEMENTASI POLA PELAYANAN YESUS SEBAGAI PELAYAN MENURUT INJIL MATIUS 4:23 - Marthen Luther Mau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
In this article, the writer narrates the story of Jesus implementing a mission in Galilee, namely teaching true teaching, preaching the Good News of God's Kingdom, healing the sick, and serving people with physical weaknesses. The mission of Jesus in all regions located in Galilee aims so that long lost mankind can hear the true teachings being taught and the Good News being proclaimed, so that those who believe in and accept Jesus can be healed of every disease and physical weakness they have suffered for a long time. To find out the mission of Jesus according to the text of Matthew 4:23, the method used in this study is a qualitative research method, with an exegetical study approach. The analysis process carried out by the author is exegesis of the biblical text and analyzing reliable secondary sources to produce accountable studies. The results of this study found that the servants of Jesus Christ must teach the correct teaching, preach the Good News of the Kingdom of God / Heaven, heal the sick, and serve people who suffer from physical weaknesses in His will. So through exegetical studies to get the author's intent from the original language text, so that the text can be understood by today's readers so that it can be implemented by the servants of Jesus Christ continuously at all places of service, whether in church, school, or in the community.